Delay in the diagnosis and treatment of cervical cancer patients treated by the Unified Health System in a reference center in Southern Brazil - Cim Asssenço, Karine; Garabeli Cavalli Kluthcovsky, Ana Claudia; Postiglione Mansani, Fabio (O Mundo da Saúde, 2017)
The purpose of this study was to identify possible delays between the suspected diagnosis, the definitive diagnosis and the beginning of treatment in patients with cervical cancer treated by the Unified Health System in a reference center for cancer treatment in southern Brazil. This is a retrospective descriptive study of a series of 222 cervical cancer cases referred for treatment between August 2003 and July 2013. Data were collected from medical records, including sociodemographic, clinical and time intervals between suspicion, diagnosis and the beginning of treatment. Among the 95 patients who started the clinical picture with an abnormal Pap smear, only 27.4% performed a biopsy within 60 days of the examination. Only 19.3% of the 57 patients who started the clinical symptoms of the disease performed the biopsy within 60 days after the onset of symptoms. From the total number of patients, only 37.8% started treatment within 60 days after the biopsy result, and 15.3% took more than 180 days to start treatment. It was concluded that there was a delay between the suspected diagnosis and the biopsy, as well as the beginning of the treatment. Strategies to reduce the time for diagnosis and treatment of the disease should be prioritized.